Language means of emotional influence in modern English publicistic texts - Saiko, Nina (Global Prosperity, 2022)
The article is dedicated to the topical issue of manipulative technologies as a method of influencing the recipients’ consciousness in modern publicistic texts. The work focuses on linguistic means used to change the reader’s emotional state in English-language mass media. Although it is believed that official information sources should stay neutral and cover the news impartially, in practice everything happens differently. Thus, there is a tendency to have a hidden impact on the addressee’s cognitive activity. The language manipulation has been defined as the selection and further implementation of those language means that most effectively influence the addressee in a certain situation and circumstances. The article presents various levels and methods of language manipulation: lexical, phonetic, grammatical, and graphic, which differ in different means of implementation. Thus, at the lexical level, the author uses various lexical units, synonyms, paronyms, euphemisms, etc.; on the phonetic – an associative series of sounds and letters, rhyme, etc.; on grammar – different types of sentences (passive, impersonal, conditional) and grammatical units; on the graphic – visual presentation of information. During the analysis, seven types have been identified as the main methods of emotional influence: 1) use of various epithets; 2) exercise the natural language of the author of the message; 3) implementation of impersonal and passive constructions; 4) metaphorical statements and personification; 5) euphemisms and dysphemisms; 6) figurative comparative constructions; 7) a significant number of modal verbs. Through epithets, the addressee can control the emotions that their address evokes in the addressees without drawing attention to the process itself. It has been found that direct speech enables the inclusion of a sufficient number of stylistic and rhetorical figures in the publicistic text. Impersonal and passive constructions make it possible to provide information implicitly, giving the reader the feeling of a neutral information presentation. Metaphorical statements are necessary to emphasize the required data. Euphemisms and dysphemisms help avoid a direct adverse reaction and “smooth out sharp corners.” Modal verbs and figurative comparative constructions also sharpen attention at the necessary points, reflecting both positive and negative attitudes of the author of the journalistic text.